Properties of hot-pressed lithium silicate glass-ceramics. Issue 5 (May 2019) - Hallmann, Lubica; Ulmer, Peter; Gerngross, Mark-Daniel; Jetter, Justin; Mintrone, Michaël; Lehmann, Frank; Kern, Matthias
Abstract: Objectives: New lithium silicate/disilicate hot-pressed glass-ceramics are introduced into the dental market. It is known that the mechanical properties of this material depend on the microstructure, chemical composition, glass matrix, morphology of crystals, volume ratio crystal/glass, additive, and treatments. This contribution investigates how these factors affect the properties of the new generation of lithium silicate/disilicate hot-pressed glass-ceramics. Methods: Three lithium silicate/disilicate hot-pressed glass-ceramics were investigated; IPS e.max Press (control group), Initial LiSi Press and Celtra Press. The specimens were prepared according to the manufacturers` instructions. Different methods; DTA, XRD, Raman, optical spectroscopy, SEM were used to characterize the properties of these materials before, after heat and etching treatments. The heat treatments (four firings) were performed according to the manufacturer's instructions (GC company) for veneering (initial LiSi) of LS2 glass-ceramics. The etching was performed according to the manufacturer's instruction. Vita ceramics etch gel (HF 5%) was used as an etching agent. The mechanical properties were investigated according to DIN EN ISO 6872:2015 and ASTM C 1327-08 instructions. Results: DTA and XRD analysis revealed that the transformation of the lithium silicate (LS) phase to the LS2 phase was completed for IPS e.max and Initial LiSi Press ingots while for Celtra Press ingots it was not. After pressing, the rod-shaped crystals were aligned parallel to the extrusion direction, while the platelet-shaped crystals having an interlocking microstructure were not. The mechanical properties depend on the microstructure, the chemical composition, the crystals morphology, the volume crystal/glass ratio, and the treatments (heat and etching). ZrO2 did not improved the mechanical properties. Etching with HF gel decreased the flexural strength. After four heat treatments, the biaxial flexural strength, the KIC, the roughness and the optical properties were affected. According to the HT-XRD, IPS e.max Press ingots can be hot pressed up to 900 °C, the initial LiSi Press ingots up to 940 °C and Celtra Press ingots up to 880 °C. Significance: The properties of LS2 glass-ceramics depend on the chemical composition, the microstructure, the morphology of the crystals, the properties of the residual glass matrix, the volume ratio of crystal/glass, and the treatments (heat and etching).